Unexpectedly long intravenous and intracardiac extension of a small-sized pulmonary pleomorphic carcinoma - Ishii, Aya; Kimura, Tokuhiro; Moritani, Koshiro; Cui, Dan; Tanaka, Shinsuke; Kawano, Hiroo; Ikeda, Eiji (Journal of Thoracic Disease, 2014)
Pleomorphic carcinoma of the lung is one of the uncommon histological types of lung cancers, which shows an aggressive behavior. Intravenous extension (not metastasis or direct invasion) of the tumor into the heart is a rare complication of lung cancers. We present a case of a 64-year-old man, who was admitted to hospital due to severe dyspnea. Chest CT scan revealed a 2-cm nodule in the upper lobe of the right lung. Echocardiography demonstrated a giant mass in the left atrium. Because of a considerable distance between the lung nodule and heart, the relation of these two lesions was unclear. He died four days after the admission. At autopsy, the lung nodule was pleomorphic carcinoma composed of spindle and giant cells, which invaded the pulmonary vein and extended intravenously to the left atrium. The intravenous component of the tumor measured approximately ten cm in length. At the tip of the extension, an 8 cm × 5 cm × 3 cm mass was formed in the left atrium, which obstructed the mitral valve. This case highlights a possibility that even a small-sized, peripherally located pleomorphic carcinoma of the lung could extend for an unexpectedly long distance to the heart, causing cardiac complications.